Integrating robust feature selection with deep learning for ultra-high-dimensional survival analysis in renal cell carcinoma - Shaymaa Mohammed Ahmed; Majid Khan Majahar Ali; Raja Aqib Shamim (Journal of Nigerian Society of Physical Sciences)
The research method applies robust feature selection approaches to ultra-high-dimensional survival data records from Renal Cell Carcinoma patients through deep learning methodologies. The linear methods LASSO and Elastic Net encounter failure when processing data because they face simultaneous multicollinearity issues in addition to overfitting effects and produce marginal survival outcome variability prediction at 54%. We suggest combining ISIS with deep learning architectures featuring PCA-RFA-RSIS models as a remedy to handle these present limitations. Among all evaluated methods PCA-RFA-RSIS is proved most accurate with an MSE measurement of 24.39 and R2 value of 0.89. PCA improved the model’s dimensionality reduction power and robust ISIS maintained model stability despite outliers present in the data. The discovery holds significant value in precision medicine because it creates opportunities to develop individualized therapy for kidney failure patients. Further research needs to enhance hybrid models and expand their utilization between different diseases as well as complex biological systems.